Media Communications of the Region in Context of Globalization and Glocaliza-tion of Information Space (on Example of Mass Media of the Republic of Mordovia) - K. V. Dementieva (Научный диалог, 2020)
The article analyzes the impact of globalization processes on the development of information and communication potential of mass media in the Republic of Mordovia. Such concepts as “globalization,” “information and communication globalization,” “content of the epoch,” “acceleration of the rhythm of time,” “glocalization” are clarified and justified. The positive and negative consequences of the impact of glocal processes on the development of the region are presented. The author summarizes the research on new media and the processes of digitalization of the information system and highlights the main factors of globalization in regional media. There is a quantitative growth of mass communication media in the Republic of Mordovia and the development of the entire system of media communications. It is proved that globalization in the media of the Republic of Mordovia, as well as in other regions, is carried out through digitalization, which is represented in all information processes, while glocalization is manifested in the preservation of regional and national characteristics. Based on the thematic analysis of the media texts of Mordovia, it is shown that the vast majority of materials are devoted to events in the region, that is, on the one hand, the audience remains highly interested in regional topics, and on the other hand, regional news reaches the federal and even global level. It is noted that the federal network media does not manage to take a significant place in the region and this gives scope for the development of the local press.